Optimasi Industri Peternakan Ayam Broiler Di UD. Sumber Urip Kabupaten Jember - Nesfian, Dwi Apink Dela; Nelly Budiharti; Mariza Kertaningtyas (Jurnal Serambi Engineering, 2026)
UD. Sumber Urip is a UMKM engaged in broiler chicken farming. As market demand for chicken meat continues to rise, the implementation of proper broiler farm management must also be improved. The analysis was conducted using the FMEA method to identify risks based on the RPN value, followed by developing priority improvement proposals using the 5W+1H method. Optimization of harvest output was then analyzed using Linear Programming based on the proposed improvements. The data results show that the highest RPN values in the FMEA assessment were feed not meeting standards and age-phase mismatch, with an RPN of 225, and chicken density not being properly calculated, with an RPN of 240. The proposed improvements focus on aligning the appropriate amount of feed and considering proper stocking density. Furthermore, the optimization analysis using Linear Programming with POM-QM software produced the following results: the initial condition yielded 50,866 kg, condition 1 yielded 50,866 kg, condition 2 produced 55,029 kg, and condition 4 produced 54,638.7 kg. Condition 2 was identified as the most optimal, where House A required 6,500 kg of S00 feed, 15,000 kg of S11 feed, and 38,000 kg of S12 feed with a density of 14 chicken/m². Meanwhile, House B required 4,000 kg of S00 feed, 7,500 kg of S11 feed, and 19,000 kg of S12 feed with a density of 13 chicken/m².